Companion species
1 online resource (xvi, 256 pages)
Keywords: "This book explores the connection between saints and animals, and how the power over animals has been a characteristic of saints from their beginnings in the Early Church. The connection between saints and humans is examined, with the saint as a human rising beyond humanity, touching the divine, and the non-human animal as a creature, which is connected to and yet removed from humanity and which may have a connection to the sacred itself. This volume transcends traditional religious boundaries by including Christian saints as well as similar figures in Islam and Norse religions. It operates on the cusp of two exciting and innovative fields: hagiographic and animal studies. It shows the complexities of human-animal interaction and the sacred: authorities clashing with experiential knowledge, metaphorical animals as opposed to real, animals ranging from helpers or opponents of saints, disguises of demons, or identity markers of a human community. Companion Species will be of value to scholars and students interested in medieval history, Europe and religion, as well as social and cultural history"--